Enamel lesions: Meta-analysis on effect of prophylactic/therapeutic agents in erosive tissue loss - Liliana Teixeira; Patrícia Manarte-Monteiro; Maria Conceição Manso (Elsevier, 2016)
This study aims to perform a meta-analysis on the effect of prophylactic/therapeutic agents in enamel tissue loss due to erosion. A paper search was done on Medline, PubMed, Embase, and Cochrane Library, and 732 papers were identified. The inclusion criteria were very restrictive in order to be able to compare different protocols and methodologies used on those studies. Sixteen papers were eligible, grouped according to the measurement method of enamel tissue loss, and a meta-analysis was done for each type of fluoride- and casein-based agent applied. Standardized mean differences were pooled across studies. There was a significant difference between all the treatment groups and their respective control groups. The highest standardized mean difference on enamel tissue loss (mean; 95% confidence interval) was obtained by stannous fluoride (4.789 μm; 1.968-7.610; P < 0.001), followed by amine fluoride (2.485 μm; 0.746-4.225; P < 0.010), and titanium tetrafluoride (1.787 μm; 1.106-2.469; P < 0.001); the lowest difference was obtained by casein phosphopeptide-amorphous calcium phosphate (0.869 μm; 0.007-1.731; P < 0.050) and sodium fluoride (0.820 μm; 0.417-1.223; P < 0.001). Stannous fluoride as a fluoride-based prophylactic/therapeutic agent allowed the lowest enamel tissue loss in erosive conditions. Standardization among future study protocols will allow better comparison regarding the prophylactic/therapeutic agent with the best clinical efficacy.